Pharmacoeconomic Evaluation and Clinical Outcome of the Use of Channa Products as an Adjuvant in Human Albumin Therapy 20% in Ileus Patients: A Cost-Effectiveness Analysis (CEA) at Imelda Pekerja Indonesia Hospital - Alex Handani Sinaga; Milda Yanti; Guntur Berlian; Asep Aripin (SEAN Institute, 2026)
Hypoalbuminemia is a complication that is often found in ileus patients and is associated with an increased risk of complications, length of hospitalization, and the burden of treatment costs. Human albumin therapy is effective but high-cost, so pharmacoeconomic studies are needed on alternative therapies based on snakehead fish extract (Channa striata). This study aims to evaluate the cost-effectiveness and clinical outcomes of the use of Channa products as an adjuvant in 20% Human Albumin therapy in ileus patients with hypoalbuminemia at Imelda Pekerja Indonesia Hospital Medan. The study used an observational analytical design with retrospective data collection of 49 patients who were grouped into three therapy groups: Channa single, Human Albumin 20% single, and a combination of both. Effectiveness is measured using length of stay (LOS) as a proxy for therapy success, while cost is calculated from the direct cost of treatment. Cost effectiveness analysis was carried out through the calculation of Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER). The results showed the lowest average direct cost in the single Channa group (IDR 10,155,201) and the highest in the single 20% Human Albumin (IDR 39,806,166). The lowest ACER value was for the single Channa group (Rp 1,846,400 per day of treatment), and in the ICER calculation, the combination group was dominant over the 20% single Human Albumin and the single Channa group was dominant against the other two groups. It was concluded that Channa-based therapy is the most cost-effective option for the correction of hypoalbuminemia in ileus patients, while Human Albumin 20% remains important in severe conditions that require rapid correction prior to surgical procedures.